The transcriptome analysis on urea response mechanism in the process of ergosterol synthesis by Cordyceps cicadae - Qihui Su (Nature Portfolio, 2021)
Abstract Nitrogen source is required for the growth of Cordyceps cicadae and involved in the regulation of metabolite synthesis. In order to further investigate the regulatory effects of nitrogen sources on the ergosterol synthesis by C. cicadae. We first confirmed that urea could significantly increase the ergosterol synthesis. The transcriptome analysis showed that compared with biomass cultured in the control fermentation medium (CFM), 1340 differentially expressed genes (DEGs) were obtained by Gene Ontology (GO) annotation, and 312 DEGs were obtained by Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation from the biomass cultured in CFM + CO(NH2)2. Urea up-regulated D-3-phosphoglycerate dehydrogenase gene transcription level and down-regulated enolase and L-serine/L-threonine ammonialyase gene transcription level, increased serine synthesis, allosterically activate pyruvate kinase, to promote the synthesis of pyruvate and CH3CO ~ SCOA, the primer of ergosterol; Urea increase the genes transcription related with ergosterol synthesis by up-regulating the steroid regulatory element binding protein gene transcription levels. The transcriptome results were provided by those of qRT-PCR. Collectively, our finding provided valuable insights into the regulatory effect of nitrogen source on the ergosterol synthesis by C. cicadae.